ДИАЛОГ О НЕКОТОРЫХ СУЩНОСТНЫХ АСПЕКТАХ КОНСТРУКТИВИЗМА (Filološke studije, 2019)
The paper consists of a dialogue between a representative of constructivistic epistemology (or so called «participatory position») and a «devil’s advocate» who tries to examine and test different aspects of this position. Through dialogue, some of the characteristics of participatory position are presented, and some of its problems are addressed.